Integrating Procedural Justice and Budget Participation in Islamic Public Governance: Implications for Sharia-Based Managerial Performance - Lia Rachmawati; Rendy Mirwan Aspirandi; Inneke Putri Widyani (IQTISHODUNA: Jurnal Ekonomi Islam, 2025)
The purpose of this study is to examine the effects of budget participation, budget procedural fairness, and organizational commitment on sharia-based managerial performance, with budgetary slack as a mediating variable. The research method employs a quantitative approach using Structural Equation Modeling–Partial Least Squares (SEM-PLS) based on survey data from public sector organizations. The results show that budget participation and budget procedural fairness have a positive and significant impact on sharia-based managerial performance, while organizational commitment has no direct effect. Budget procedural fairness and organizational commitment positively affect budgetary slack, and budgetary slack positively influences managerial performance, but does not mediate the relationships among variables. The theoretical and practical implications highlight the role of goal clarity and procedural justice in enhancing sharia-based performance, supporting Goal-Setting Theory and Path-Goal Theory. From a policy perspective, the findings underscore the importance of participatory and fair budgeting systems in Islamic public governance to promote accountability and public welfare. The novelty of this study lies in integrating behavioral organizational theories with sharia-based managerial performance, contributing to the advancement of Islamic economics and global public governance literature.